Final report on productivity challenge 5 : developing leadership and entrepreneurship skills in small firms : how can anchor institutions support the development of small firms in their local economy? /: developing leadership and entrepreneurship skills in small firms : how can anchor institutions support the development of small firms in their local economy?. ([2016]) - Thom, Graham; MacLeod, Katie; Hope, Hannah
No abstract available